I cambiamenti di lungo periodo nelle diseguaglianze di reddito nei paesi industrializzati. (With English summary.) - Atkinson, A; Brandolini, A (2004)
The paper examines the long-run evolution of income distribution in eight industrialized countries. No common trend is observed in the last quarter of a century: the inequality of disposable incomes increased in the United States and the United Kingdom in the 1980s, and in Sweden and Finland in the 1990s; it changed little in Canada, France and the Federal Republic of Germany; it showed no clear tendency in Italy. The time patterns depend on the definition of income and, in particular, on whether taxes and benefits are included. The study of long-run changes in/inequality in advanced economies cannot neglect the redistributive impact of the public budget.